In search of academic identity : physical education, sport science and the field of human movement studies - Reppold Filho, Alberto Reinaldo (2000)
This thesis addresses the problem of the academic identity of the area traditionally referred to as physical education. The study is a critical examination of the argu ments for the justi cation of this area as an autonomous branch of knowledge. The investigation concentrates on a selected number of arguments. The data collection comprised articles books and proceedings of conferences. The preliminary assessment of these materials resulted in a classi cation of the arguments into three groups. The rst group comprises the arguments in favour of physical education as an academic discipline. The second includes the arguments supporting a science of sport. The third consists of the arguments in favour of to a eld of human movement study. The examination of these arguments produced the following results. (a) The area of physical education does not satisfy the conditions presupposed by the de nition of academic discipline. This is so because the area does not form an integrated system of scienti c theories. (b) The same di culty emerges from the examination of the ar guments for sport science. There is no science of sport because there is no integrated system of scienti c theories related to sport. (c) The arguments in favour of a eld of study yielded more productive results. However di culties arise from the de nition of human movement. The analysis of this concept showed that its limits are not well demarcated. This makes it problematic to take human movement as the focus of a eld of studies. These aspects led to the conclusion that such things as an academic discipline of physical education sport science and eld of human movement studies do not exist. At least there are not such things in the sense of autonomous branches of knowledge. This does not imply that a more integrated inquiry based on several disciplines is not possible and desirable. This would enable someone entering phys ical education to nd a more organised structure of knowledge with some generally accepted problem situations procedures and theories on which to base professional practice.